2021
DOI: 10.1002/sctm.21-0022
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts on Endothelial Stem Cells Definition, Location, and Markers

Abstract: Ischemic vascular disease is a major cause of mortality and morbidity worldwide, and regeneration of blood vessels in perfusion-deficient tissues is a worthwhile therapeutic goal. The idea of delivering endothelial stem/progenitor cells to repair damaged vasculature, reperfuse hypoxic tissue, prevent cell death, and consequently diminish tissue inflammation and fibrosis has a strong scientific basis and clinical value. Various labs have proposed endothelial stem/progenitor cell candidates. This has created con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 65 publications
1
33
0
1
Order By: Relevance
“…All these notable findings need to be involved in EPC classification for the development of an updated consensus since the current consensus on EPC nomenclature has not covered all EPCs [ 3 ] by (1) source of origin; (2) and most of the surface molecules to characterizes EPC use are from murine model findings [ 78 ], and we strongly discourage from putting these in the same line as a human EPC marker; and (3) in vivo presence, and (4) some misleading information, which we addressed in this manuscript.…”
Section: Unresolved Issues and Future Perspectivesmentioning
confidence: 99%
“…All these notable findings need to be involved in EPC classification for the development of an updated consensus since the current consensus on EPC nomenclature has not covered all EPCs [ 3 ] by (1) source of origin; (2) and most of the surface molecules to characterizes EPC use are from murine model findings [ 78 ], and we strongly discourage from putting these in the same line as a human EPC marker; and (3) in vivo presence, and (4) some misleading information, which we addressed in this manuscript.…”
Section: Unresolved Issues and Future Perspectivesmentioning
confidence: 99%
“…In addition, Ingram et al found that a complete hierarchy of EPCs can be identified in human umbilical vein ECs or human aortic ECs, showing that EPCs may originate from blood vessels ( 19 ). EPCs have been found to reside in the vasculature beds of various tissues, and CD157 or EPCR have been proposed as markers to identify tissue-resident EPCs ( 20 ). Surprisingly, a recent study reported marker genes, secreted factors, microRNAs (miRNAs), and growth factors of EPCs on the basis of single-cell transcriptomic analyses to better optimize and characterize the EPC subpopulation in adult PB.…”
Section: The Definition Origin and Biological Significance Of Epcsmentioning
confidence: 99%
“…Thus, the most frequently used markers, so far, are CD34, VEGFR-2, CD31, CD144, and CD146. Among them, CD34 alone appears as the top cell marker of identification, while the combination between CD34 and VEGFR-2 is the second most common identity [ 51 ].…”
Section: Circulating Endothelial and Progenitor Cellsmentioning
confidence: 99%